Gestational inhalation of nanoparticles alters placental glucose transporter expression and increases glucose flux in rats - Talia N. Seymore; Sara Hoffmann; Pedro Louro; Carol Gardner; Michael J. Goedken; Phoebe A. Stapleton (Toxicology and Applied Pharmacology, 2026)

Polystyrene nanoplastics disrupt mouse placenta development in a sex-dependent manner - Hanin Alahmadi; Allison Harbolic; Christopher De Oliveira-Cordova; Raulle Reynolds; Michelle Jojy; Courtney Potts; Sofia Doan; Tanvi Mathur; Mohammad Saiful Islam; Melisa J. Andrade; Quinton Smith; Phoebe A. Stapleton; et al. (Reproductive Toxicology, 2026)

Erratum to ‘Gestational inhalation of nanoparticles alters placental glucose transporter expression and increases glucose flux in rats’ [Toxicol. Appl. Pharmacol. 515 (2026) 117996] - Talia N. Seymore; Sara Hoffmann; Pedro Louro; Carol Gardner; Michael J. Goedken; Phoebe A. Stapleton (Toxicology and Applied Pharmacology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Gestational exposure to micro and nanoplastics differentially impacts cardiac development and function in male and female rats throughout the lifespan - Chelsea M. Cary; Samantha Adams; Gina M. Moreno; Talia N. Seymore; Marianne Polunas; Michael J. Goedken; Xiang Wang; Edward J. Yurkow; Phoebe A. Stapleton (Toxicology and Applied Pharmacology, 2025)

Rapid detection of microplastics and nanoplastics in seconds by mass spectrometry - Mengyuan Xiao; Yongqing Yang; Hanin Alahmadi; Allison Harbolic; Gina M. Moreno; Terry Yu; Jerry Liu; Alex Guo; Genoa R. Warner; Phoebe A. Stapleton; Hao Chen (Journal of Hazardous Materials, 2025)

Identification of micro- and nanoplastic particles in postnatal sprague-dawley rat offspring after maternal inhalation exposure throughout gestation - Gina M. Moreno; Tanisha Brunson-Malone; Samantha Adams; Calla Nguyen; Talia N. Seymore; Chelsea M. Cary; Marianne Polunas; Michael J. Goedken; Phoebe A. Stapleton (Science of The Total Environment, 2024)

Metal Nanomaterial Toxicity Variations Within the Vascular System - Alaeddin B. Abukabda; Phoebe A. Stapleton; Timothy R. Nurkiewicz (Current Environmental Health Reports, 2016)

Pulmonary Cerium Dioxide Nanoparticle Exposure Differentially Impairs Coronary and Mesenteric Arteriolar Reactivity - Valerie C. Minarchick; Phoebe A. Stapleton; Dale W. Porter; Michael G. Wolfarth; Engin Çiftyürek; Mark Barger; Edward M. Sabolsky; Timothy R. Nurkiewicz (Cardiovascular Toxicology, 2013)